ANALISIS PENYEBAB PROKRASTINASI AKADEMIK MATEMATIKA SISWA SMA SEDERAJAT SAAT PEMBELAJARAN DARING - Rahayu, Aninda Aulia; Hidayati, Fina Hanifa (Jurnal Karya Pendidikan Matematika, 2021)
Covid-19 has made learning activities that are usually held at school replaced at home by using an internet connection. Complaints from students during learning at home are a lot of tasks and because learning activities held at home making students sometimes like to delay doing tasks. The purpose of this study was to determine the causes of mathematics academic procrastination during home learning by high school students. Data retrieval was carried out by distributing questions containing short questions with 22 students as respondents. result of the research is the cause of student procrastinating are how the teacher teaches, smartphone, and other external factors such as home condition and internet connections.